The effect of thermomechanical environment on the shrinkage and warpage in thermoplastic parts - Alves, P. S. (2008)
During the injection moulding process, the material is subjected to successive transformations, being submitted to a thermo-mechanical environment that determines the final dimensions of the part. This environment is characterized by several parameters which are related to material properties, the mould design, equipment and process variables. As a result, deviations of the dimensions of the moulded parts from the dimensions of the cavity cannot be avoided. If differences on shrinkage occur, caused for example by anisotropies of the material or non-uniform cooling, distortions will happen. In order to predict this two effects on the injection cycles is require one strategy to monitoring and control the process variables. The aim is to achieve highest quality control of all manufacture parts. This paper presents the effect of different holding pressures and mould temperatures on shrinkage and warpage in two different materials, one amorphous (PC) and another semi crystalline (PP). An instrumented mould was manufactured. During the injection moulding process sensors signals were continuously monitored by a Data Acquisition System. The experimental results were compared with predictions made by commercial software.